2022
DOI: 10.3390/insects13050446
|View full text |Cite
|
Sign up to set email alerts
|

Edible Insect Farming in the Context of the EU Regulations and Marketing—An Overview

Abstract: Insects are increasingly being considered as an attractive source of protein that can cater to the growing demand for food around the world and promote the development of sustainable food systems. Commercial insect farms have been established in various countries, mainly in Asia, but in Europe, edible insects have not yet emerged as a viable alternative to traditional plant- and animal-based sources of protein. In this paper, we present an interdisciplinary overview of the technological aspects of edible insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 83 publications
(114 reference statements)
0
36
0
Order By: Relevance
“…Killing insects from their natural environment is considered irrational, a destruction of natural resources, and has many limiting factors. For this reason, large-scale farming of edible insects is a reasonable and viable option [ 251 ]. The purpose of human insect farming is to make edible insects better able to meet human needs for nutrition and health.…”
Section: Factors To Consider In the Consumption Of Edible Insectsmentioning
confidence: 99%
“…Killing insects from their natural environment is considered irrational, a destruction of natural resources, and has many limiting factors. For this reason, large-scale farming of edible insects is a reasonable and viable option [ 251 ]. The purpose of human insect farming is to make edible insects better able to meet human needs for nutrition and health.…”
Section: Factors To Consider In the Consumption Of Edible Insectsmentioning
confidence: 99%
“…Based on a review of the literature done by Żuk-Gołaszewska et al [ 34 ], they concluded that edible insect farming can be a viable business sector that significantly contributes to the overall sustainability of food systems if appropriate regulations are introduced and food safety standards are guaranteed. However, the success of the edible insect industry also requires consumer acceptance of entomophagy, which is rather low in Western societies.…”
Section: Reviewmentioning
confidence: 99%
“…Insect production may raise concerns, as it is a new and developing method of food production. High levels of pathogens or other contaminants, such as heavy metals found in the feed used in insect farming, may be the main vector of contamination for insects intended for human consumption [ 4 , 23 ]. Not to mention, insects may be considered an allergen concern.…”
Section: Introductionmentioning
confidence: 99%
“…Insects have a similar protein profile to shellfish/crustaceans that may cause allergic responses in certain individuals [ 24 , 25 ]. However, these concerns may be managed through regulations on agricultural feed, and preventative controls such as HACCP procedures and required labeling on insect-based foods [ 4 , 23 ]. Requirements for high-quality feed for insects intended for human food may lead to higher production costs when compared to conventional animal meat production [ 26 ].…”
Section: Introductionmentioning
confidence: 99%